Mitochondria in Focus: From Function to Therapeutic Strategies in Chronic Lung Diseases - Caldeira, Dayene de Assis Fernandes; Weiss, Daniel J.; Rocco, Patricia Rieken Macêdo; Silva, Pedro Leme; Cruz, Fernanda Ferreira (Frontiers in Immunology, 2021)
Mitochondria are essential organelles for cell metabolism, growth, and function. Mitochondria in lung cells have important roles in regulating surfactant production, mucociliary function, mucus secretion, senescence, immunologic defense, and regeneration. Disruption in mitochondrial physiology can be the central point in several pathophysiologic pathways of chronic lung diseases such as chronic obstructive pulmonary disease, idiopathic pulmonary fibrosis, and asthma. In this review, we summarize how mitochondria morphology, dynamics, redox signaling, mitophagy, and interaction with the endoplasmic reticulum are involved in chronic lung diseases and highlight strategies focused on mitochondrial therapy (mito-therapy) that could be tested as a potential therapeutic target for lung diseases.